Farmakoterapija depresivnih motenj - Bačar, Cvetka (Farmacevtski vestnik, 2006)
Although antidepressants have been available for about 50 years we still have lots of gaps in our knowledge about their therapeutic mechanisms. They should be used for any of the three phases of treatment of depressive disorders. The goal of acute treatment is to eliminate or allviate the symptoms of an active episode. The goal of maintenance treatment is to prevent a relaps after the alleviation of symptoms. The goal of prophylactic treatment is to prevent the future reoccurrence of new depressive episodes. If we wont drug treatment to be efficient and acceptable to patient, we need to diagnose and to treat depressive disorders as soon as possible. We should be aware of advantages, limitations and therapeutic mechanisms of antidepressants and use individualized antidepressant medication.
Keywords: Antidepresivi; Antidepressive Agents; Depresija; depresija (medicina); Depression; drug; drug therapy; zdravila; Zdravljenje z zdravili